+0  
 
0
5
1
avatar+354 

Let a and b be the solutions to 7x^2 + x - 5 = -3x^2 - 9x - 4. Compute (a - 4)/(b - 4) + (b - 4)/(a - 4).

 Jun 22, 2024
 #1
avatar+129725 
+1

Simplify as

 

10x^2 + 10x - 1   =  0 

 

ab =  -1/10

 

a + b =  -10/10  = -1     square both sides

 

a^2 + b^2 + 2ab  = 1

 

a^2 + b^2  = 1 - 2(-1/10)  =  1+ 2/10  =1 + 1/5 =    6/5

 

 

(a - 4) / (b -4)  +  (b -4) / ( a - 4)  =  

 

[ (a - 4)^2 + ( b -4)^2 ]  /  [ (a - 4)(b - 4)]  = 

 

[ (a^2 + b^2 - 8 (a +b) + 32 ]  / [ ab - 4(a + b)  + 16]  =

 

[ 6/5 - 8 (-1) + 32 ] / [ -1/10 - 4 (-1) + 16 ]  =

 

[ 6/5 + 40 ]  / [ 20 - 1/10]  =

 

412 / 199

 

cool cool cool

 Jun 22, 2024

1 Online Users